Ice Thickness and Bed Elevation of the Northern and Southern Patagonian Icefields. Issue 12 (17th June 2019) - Millan, R.; Rignot, E.; Rivera, A.; Martineau, V.; Mouginot, J.; Zamora, R.; Uribe, J.; Lenzano, G.; De Fleurian, B.; Li, X.; Gim, Y.; Kirchner, D.
Abstract: The Northern and Southern Patagonian Icefields are the largest ice masses in the Southern Hemisphere outside Antarctica, but their ice volume and bed topography are poorly known. Here, we combine airborne gravity data collected in 2012 and 2016, with radar data from the Warm Ice Experiment Sounder and Centro de Estudios Científicos's to map bed elevation and ice thickness in great detail. We perform a 3‐D inversion of the gravity data constrained by radar‐derived thickness and fjord bathymetry to infer bed elevation at 500‐m spacing, with a precision of about 60 m. We detect deep glacial valleys with ice thickness exceeding 1, 400 m and sectors below sea level on the western branch of Glaciar Pio XI, Occidental, between San Rafael and Colonia, and near Fitz Roy. We calculate an ice volume of 4, 756 ± 923 km 3 for Northern Patagonia Icefield and Southern Patagonia Icefield, or 40 times the volume of glaciers in the European Alps. Plain Language Summary: Traditional techniques of radar depth sounding fail to resolve thick, temperate ice masses due to poor penetration of the radar signals into snow and ice and extensive scattering due to water content. We combine sparse airborne radar sounding and bathymetry data with novel high‐resolution, high‐precision airborne gravity data to infer the bed topography of the Patagonia Icefields of South America. The results reveal the full range of deep ice thickness on the plateau, portions of the icefields grounded below sea level, and the total volume content of the Patagonia Icefields. The results are critical to constrain the details of the past, present, and future evolution of this glaciated region in a warmer climate. Key Points: Comprehensive ice thickness and bed elevation measurements are conducted on the Northern and Southern Patagonian Icefields of South America Ice thickness in excess of 1, 400 m is observed over selected regions of the plateau A multisensor approach solves the problem of mapping the thickness of temperate ice masses